SIFAT KIMIA DAN TINGKAT KESUKAAN PERMEN KERAS (Hard Candy) SARI BUAH PALA (Myristica fragrans houtt famili myristicaseae) - Claudya A Tamaka; Gregoria S.S. Djarkasi; Judith S.C. Moningka (Universitas Sam Ratulangi, 2016)
ABSTRACTOne alternative meat processing nutmeg namely confectionery products, meat nutmeg can be made as hard candy or soft candy. (Anonymous, 2010). Chewing is a food product that is much-loved. The purpose of this study was to determine the proportion of nutmeg juice and water as the manufacture of candy nutmeg and evaluate the level of preference panelists include taste, odor and color. The results showed that a hard candy (hard candy) nutmeg best and most preferred by the panelists are on treatment A (100% juice nutmeg) with the average value of a sense of 4.00 (like), bau3.74 (like) color 3.79 (love). The test results showed that the water content of proximate hard candy nutmeg (0.54%), hard candies nutmeg sugar (67.60%) and acidity (pH) candy nutmeg (4:02%).Keyword :) Nutmeg fruit juice, Candy, Glucose